SAE Technical Paper Series 2008
DOI: 10.4271/2008-01-2094
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Structured Sorbents for the Adsorption of Carbon Dioxide and Water Vapor from Manned Spacecraft Atmospheres: Applications and Modeling 2007/2008

Abstract: In NASA's Vision for Space Exploration, humans will once again travel beyond the confines of earth's gravity, this time to remain there for extended periods. These forays will place unprecedented demands on launch systems. They must not only blast out of earth's gravity well as during the Apollo moon missions, but also launch the supplies needed to sustain a larger crew over much longer periods. Thus all spacecraft systems, including those for the separation of metabolic carbon dioxide and water from a crewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Development of highly optimized lattice monoliths is being pursued to eliminate particle generation, reduce pressure drop, and allow for direct thermal regeneration that will benefit loop closure applications. These developments are discussed in a companion paper [7].…”
Section: Overall Approachmentioning
confidence: 99%
“…Development of highly optimized lattice monoliths is being pursued to eliminate particle generation, reduce pressure drop, and allow for direct thermal regeneration that will benefit loop closure applications. These developments are discussed in a companion paper [7].…”
Section: Overall Approachmentioning
confidence: 99%
“…The intent of this configuration was to efficiently exchange heat generated from adsorption to the desorbing bed, yielding near isothermal sorption processes. The use of Al foam to transport heat from adsorbing to desorbing processes is a technique pioneered by Hamilton Sundstrand in their development of amine-based CO 2 removal systems 12 and has been developed for vacuum swing adsorption of water with silica gel in support of the Sorbent-Based Atmosphere Revitalization (SBAR) project 13 . The IBD performance testing consisted of an inlet dew point of 10 °C (50 °F) and a flow rate range of 10-17 slpm with half cycles ranging from 7-20 minutes.…”
Section: B Design For Thermal Optimizationmentioning
confidence: 99%
“…1,9 The radial design was based on a two-layer "sandwich" system consisting of a continuous layer of sorbent-coated Microlith screens and a corresponding insulating layer coated with the same sorbent material. Similar with the previous design, the insulating mesh serves as an insulating layer for isolating the Microlith layer electrically.…”
Section: A Design and Fabrication Of Regenerable Adsorber Modulementioning
confidence: 99%
“…Currently, packed beds of sorbent pellets are mostly used in the adsorption systems; however, recent studies have shown that these materials can be easily fluidized and/or eroded, due to both thermal cycling and mechanical vibration, and can generate fine particulates that bypass the downstream mesh filters. 1,2 This results in particulates buildup in downstream pumps, blowers, and other components, and has been problematic in some aerospace applications. Furthermore, these packed beds of pellets create a large pressure drop across the adsorption system resulting in high parasitic losses.…”
Section: Introductionmentioning
confidence: 99%